A TC4 titanium alloy bar for pedicle screws and a processing method thereof

By optimizing the chemical composition and microstructure structure of TC4 titanium alloy and combining with multiple processing technologies, the residual stress of titanium alloy rods for pedicle screws was successfully controlled, the problem of "mouth shrinkage" was solved, the technical requirements of the new product were met and the production efficiency was improved.

CN118639054BActive Publication Date: 2025-03-28XIAN KEEN TITANIUM NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411130301.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-28
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the residual stress of the TC4 titanium alloy rod for pedicle screws, resulting in a "mouth shrinkage" phenomenon during processing, affecting product performance and clinical application.

Method used

By optimizing the chemical composition and microstructure structure of TC4 titanium alloy, the residual stress of the titanium alloy rod is controlled to be at a lower level by using multi-fire commutation upsetting forging, β forging and two-phase zone forging, thermal drawing, complete annealing, electrical heating straightening and stress removal annealing.

Benefits of technology

It has achieved effective control of the residual stress of the titanium alloy rod for pedicle screws, reduced the "mouth shrinkage" phenomenon, met the technical requirements of the new product with a depth of 150mm U-shaped groove, and improved production efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118639054B_ABST
    Figure CN118639054B_ABST
Patent Text Reader

Abstract

The present invention relates to a TC4 titanium alloy bar material for pedicle screws and a processing method thereof, wherein the material is automatically mixed with high-quality pre-melted master alloy; the ingot is repeatedly smelted three times in a vacuum consumable arc furnace, the ingot is subjected to multi-fire reversing upsetting, and β forging and two-phase zone forging are combined at the same time, hot drawing is performed after rolling for more than two fires, the semi-finished bar material after hot drawing is heated to above the recrystallization temperature for complete annealing, and is tempered again after electric heating straightening, and is ground by multiple passes with small processing amounts. The titanium alloy bar material for medical pedicle screws produced by the present invention has excellent comprehensive performance, stable organizational state, and a U-shaped shrinkage index that can meet the technical requirements of a new product with a U-shaped groove depth of 150 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy processing, in particular to a TC4 titanium alloy bar material for pedicle screws and a processing method thereof. Background Art

[0002] As a new type of metal material, titanium alloy has been widely used in the medical field in recent years because of its low density, high specific strength, good biocompatibility and low elastic modulus. TC4 titanium alloy is currently the most widely used α+β type titanium alloy. It contains 6% α-stabilizing element Al and 4% β-stabilizing element V. It has good strength-plasticity matching and good processing performance. It is widely used in the pharmaceutical industry, medical devices, human implants and other fields.

[0003] U-shaped nails (pedicle screws) as spinal fixation systems are generally processed from TC4ELI titanium alloy bars, and are used to treat spinal fractures, lumbar fractures, slippage, spinal stenosis, deformity correction and other diseases, playing an important role in complex surgeries. Medical U-shaped nail titanium alloy bars produced by traditional processes have large residual stress, which causes them to deform during processing and forming, forming the so-called "shrinkage" (U-shaped mouth shrinks). The size and stability of the shrinkage are one of the important indicators for evaluating the performance of U-shaped nails.

[0004] Residual stress refers to the stress state maintained inside the material without external load. Residual stress may be generated during the production and use of metal materials. Residual stress has a significant impact on the performance, processing accuracy, and service life of metal materials. Therefore, how to control residual stress during the production and manufacturing process of materials is of great significance to improving product quality and performance.

[0005] Medical TC4ELI rods are processed into U-shaped nails and connecting rods with a tight fit and implanted into the human body as a spinal fixation system. However, due to the "shrinkage" reason, the connecting rod cannot be properly inserted into the U-shaped groove for clamping and positioning, which brings inconvenience to clinical applications and affects the treatment of patients. Therefore, the difficulty is to effectively control the residual stress inside the titanium alloy rods for pedicle screws to avoid the "shrinkage" phenomenon during the processing process.

[0006] At present, titanium alloy bar products for medical pedicle screws can meet the requirements of processing pedicle screws with U-groove depth of about 25~35mm. However, with the development of medical technology and the technical upgrading of medical pedicle screw products, the U-groove depth of some new pedicle screw products has reached about 100mm, and some have even reached about 150mm. The existing titanium alloy bar production technology cannot meet the requirements of the above products. Summary of the invention

[0007] The purpose of the present invention is to provide a TC4 titanium alloy rod for pedicle screws and a processing method thereof, so as to reduce the generation of residual stress during the production process and control the residual stress at a lower level to meet the demand for new medical pedicle screw products with a U-groove depth of 100-150 mm.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The invention provides a TC4 titanium alloy bar for pedicle screws. The chemical composition of the TC4 titanium alloy is calculated by mass fraction, and main components include 6.07 to 6.11% of Al, 3.98 to 4.13% of V, 0.16 to 0.19% of Fe, 0.012 to 0.015% of C, 0.008 to 0.009% of N, 0.105 to 0.122% of O, and 0.003 to 0.004% of H; the balance is Ti.

[0010] In the above-mentioned TC4 titanium alloy rod for pedicle screws, Ti is high-quality grade 0 sponge titanium.

[0011] The present invention also provides a method for processing a TC4 titanium alloy bar for a pedicle screw, using the above-mentioned TC4 titanium alloy component ratio, comprising the following steps:

[0012] Step 1: Use high-quality pre-melted master alloy to automatically mix the materials; use a vacuum consumable arc furnace to repeatedly melt three times to form a TC4 titanium alloy ingot;

[0013] Step 2: The TC4 titanium alloy ingot is subjected to three-time reversing upsetting and forging by combining β forging with two-phase zone forging, and the forging temperature is 900-1150°C;

[0014] Step 3: After forging, the steel is rolled for more than two times, with a rolling temperature of 880~950℃ and a deformation rate of ≥60%;

[0015] Step 4: After rolling, hot drawing is performed, the hot drawing deformation temperature is 870~920℃, and the deformation amount is 5%~25%;

[0016] Step 5: Heat the semi-finished bar after hot drawing to above the recrystallization temperature for complete annealing, the annealing temperature is 700~850℃, and the annealing time is 1~2h; after annealing, use furnace cooling to below 500℃ and then air cooling;

[0017] Step 6: Electric heating straightening is performed by heating and straightening, and tempering is performed again after straightening;

[0018] Step 7: Stress relief annealing, the stress relief annealing temperature is 480~700℃ and kept warm for 2~5h. After the stress relief annealing is completed, the semi-finished bar is cooled to below 150℃ with the furnace;

[0019] Step 8: Grinding is performed through multiple passes with small processing volume, and the single pass grinding volume is ≤0.15mm.

[0020] In step 2 of the above method, the temperatures of the three-fire reversing upsetting and drawing forging are 1050-1150°C, 1000-1050°C, and 900-1000°C, respectively.

[0021] In step three of the above method, the second rolling temperatures are 900-950°C and 880-930°C respectively.

[0022] The beneficial effects of the present invention are:

[0023] It has been verified that the titanium alloy rod for medical pedicle screws produced by the present invention has excellent comprehensive performance, stable tissue state, and the U-shaped shrinkage index can meet the technical requirements of a new product with a U-shaped groove depth of 150mm. Moreover, the process is simpler than the original process, the production efficiency is higher, and it has a good industrial production foundation.

[0024] The present invention starts from the mechanism of residual stress generation in the production and processing process of titanium alloy, and achieves technical indicators for controlling the shrinkage amount of two typical specifications of U-groove depth of 35mm and 150mm (end): the average shrinkage amount of U-groove depth of 35mm is not more than 0.04mm, and the average shrinkage amount of U-groove depth of 150mm is not more than 0.07mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the processing method of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] refer to Figure 1 The main reason for the generation of residual stress in titanium alloy is due to the uneven distribution of internal microstructure and the instability of the state. In order to solve the above unevenness and instability, the present invention fundamentally reduces the generation of residual stress through the following steps, thereby controlling the shrinkage of the U-shaped nail.

[0028] 1) Chemical composition control

[0029] The uniformity of chemical composition is the basis of organizational uniformity. The difference in chemical composition of different regions of the ingot will cause significant changes in the content of α and β phases in the microstructure. In order to ensure the uniformity of the composition of TC4 titanium alloy bars, the present invention uses high-quality pre-melted master alloys and advanced automatic mixing technology to ensure the uniformity of each component in the electrode block; it uses a vacuum consumable arc furnace for three repeated smeltings, and optimizes the melting rate control, stirring and solidification process control to ensure the uniformity of the ingot composition.

[0030] The distribution of impurity elements such as iron, oxygen, carbon, nitrogen, and hydrogen in the ingot will seriously affect its internal organization, and will cause the lattice of the titanium alloy to be greatly distorted, thereby affecting the stress distribution inside it. Therefore, it is necessary to strictly control the content of the above impurity elements and make them as evenly distributed as possible. In the present invention, iron and oxygen elements are added in the form of compounds so that they are more evenly distributed. In order to control other impurity contents, the present invention uses high-quality grade 0 sponge titanium, in which the impurity content is lower and the influence on the internal organization of the ingot is smaller.

[0031] The chemical composition of the TC4 ingot smelted by the present invention is shown in Table 1.

[0032] Table 1 Chemical composition of TC4 ingot

[0033] Location Al V Fe C N O H surface 6.11 4.13 0.17 0.012 0.008 0.122 0.003 Heart 6.07 4.09 0.19 0.015 0.009 0.115 0.003

[0034] 2) Microstructure control

[0035] The uniform and fine equiaxed structure has stronger stability, and the residual stress inside it is correspondingly smaller. In order to meet the above requirements, the present invention has carried out a lot of process optimization during the deformation process of titanium alloy, specifically:

[0036] Forging: The forging process adopts a multi-fire reversing upsetting and drawing process. Through multiple upsetting and drawing deformations, the structure of the titanium alloy billet is refined; at the same time, through multiple reversals, the microstructure of the billet in different directions is made more uniform; and a process combining β forging and two-phase zone forging is adopted to fully break the original β grain boundary and optimize the transformation and recrystallization process of the β phase, thereby forming a uniform equiaxed structure.

[0037] Rolling: By reasonably controlling the rolling temperature and deformation rate ≥ 60%, and coordinating the corresponding billet heat treatment plan, on the one hand, the structure of the titanium alloy billet is further refined. At the same time, by reasonably controlling the deformation temperature and controlling the internal α phase content, and coordinating the billet heat treatment, the structure is further equiaxed and homogenized, and a billet with small residual stress is produced.

[0038] 3) Hot drawing process control

[0039] The billets produced by rolling generally need to be hot drawn. The hot drawing process requires reasonable control of the deformation temperature and deformation amount by 5% to 25%. If the deformation temperature is unreasonable, secondary α phase is likely to be produced, which will adversely affect the equiaxed grains. Using a larger drawing deformation amount can further refine the grains, optimize the internal organizational structure, and control the residual stress at a lower level.

[0040] 4) Full annealing

[0041] The semi-finished bar after hot drawing needs to be heated to above the recrystallization temperature for complete annealing. Through the high annealing temperature and long annealing time, the internal grains are recrystallized to form a fine and uniform equiaxed structure, and the internal residual stress is completely eliminated. The cooling method adopts furnace cooling to avoid thermal stress generated inside the material during the rapid cooling process.

[0042] 5) Electric heating straightening

[0043] The present invention completely abandons the traditional roller straightening process in terms of straightening process, because the roller straightening process will produce a large amount of residual radial compressive stress, which is the main reason for the poor shrinkage performance of titanium alloy bars. Therefore, the present invention adopts a new electric heating straightening process, which avoids the residual compressive stress problem caused by the original process by heating and straightening; at the same time, the small amount of axial tensile stress generated by the electric heating process is eliminated by re-tempering after straightening.

[0044] 6) Stress relief annealing

[0045] The stress relief annealing temperature is selected below the recrystallization temperature. Through a long period of heat preservation, the internal structure of the titanium alloy rod is further homogenized. At the same time, through long-term heat preservation at low temperature, fine dispersed α phase is precipitated in the internal structure, so that the uniformity and stability of the structure are better, and the internal stress is further released and balanced, thereby achieving an extremely low internal stress level.

[0046] After the stress relief annealing is completed, the semi-finished bars need to be cooled to below 150°C in the furnace to avoid residual stress in the semi-finished bars due to inconsistent internal and external cooling rates during the rapid cooling process.

[0047] 7) Grinding

[0048] The semi-finished titanium rod needs to strictly control the single-pass processing amount during the grinding process to avoid the generation of processing stress due to excessive single-pass processing amount. The present invention ensures that the residual stress of the finished rod reaches the expected level.

[0049] Through the above-mentioned control of composition, microstructure and special processing technology, the residual stress control level of the titanium alloy rod for medical pedicle screws has been significantly improved. The test results also show that the U-shaped shrinkage index of the titanium alloy rod for medical pedicle screws produced by the present invention can meet the technical requirements of a new product with a U-shaped groove depth of 150 mm. Example

[0050] First, the chemical composition of the formula in Table 2 below is used for proportioning, and high-quality grade 0 sponge titanium is added and smelted repeatedly three times in a vacuum consumable arc furnace to ensure the uniformity of the ingot composition.

[0051] Table 2 Chemical composition of TC4 ingot of Example 1

[0052] Location Al V Fe C N O H surface 6.11 4.12 0.16 0.012 0.008 0.122 0.004 Heart 6.09 3.98 0.19 0.013 0.009 0.105 0.003

[0053] 2) After the ingot is ground, it is forged in three stages:

[0054] First fire: temperature T = 1050 ~ 1150 ℃, Ф620 × L mm / upsetting → Ф350 × L mm;

[0055] Second fire: temperature T = 1000 ~ 1050 ℃, Ф350 × L mm / upsetting → Ф260 × L mm;

[0056] Third fire: temperature T = 900 ~ 1000 ℃, Ф260 × L mm / upsetting → Ф150 × L mm;

[0057] 3) Ф150×L mm for second heat rolling:

[0058] First fire temperature: T = 900 ~ 950 ℃, Ф150 × L mm rolled to Ф60 × L mm;

[0059] The second fire temperature is controlled at T=880~930℃, and the Ø60×L mm is rolled to Ø15.5×L mm;

[0060] 4) Hot draw the Ф15.5×L mm semi-finished bar to Ф15×L mm, ensure the drawing deformation, the temperature is 870~920℃, further refine the grains, optimize the internal structure, and control the residual stress level.

[0061] 5) Strip the Ф15×L mm bar to Ф14.5×L mm on a centerless lathe to remove the surface oxide scale and surface defects of the bar.

[0062] 6) The Ф14.5×L mm bar is heated and recrystallized to 700~850℃ for 1~2h for full annealing process. The grains inside the billet are recrystallized to form a fine and uniform equiaxed structure, which completely eliminates the residual stress inside the structure. The cooling method adopts furnace cooling to below 500℃ and then air cooling to avoid thermal stress inside the material during the rapid cooling process.

[0063] 7) After annealing, tensile force is applied to both ends of the bar and the bar is clamped by an electric straightening machine for heating and straightening, which avoids the problem of residual compressive stress caused by the original process; at the same time, the small amount of axial tensile stress generated by the electric heating process is eliminated by re-tempering at low temperature after straightening.

[0064] 8) After the straightening by electric heating, the rod is subjected to stress relief annealing at 480~700℃ for 2~5h to further homogenize the internal structure of the titanium alloy rod. At the same time, the internal structure is precipitated with fine dispersed α phase through long-term heat preservation at low temperature, so that the uniformity and stability of the structure are better, and the internal stress is further released and balanced, thereby achieving an extremely low internal stress level. After stress relief annealing, the semi-finished rod is quickly cooled to below 150℃ with the furnace to avoid the generation of residual stress again.

[0065] 9) The straightened bars are machined, ground, and polished in multiple passes with small amounts to a finished product of Ф14.1×L mm (single pass grinding amount ≤0.15 mm).

[0066] 10) Detect the shrinkage. Take 10 sample bars with a length of 240 mm from the bar material, and process a U-shaped groove with a depth of 150 mm and a width of 6 mm along the axial direction with the center of the end face as the center. Measure the shrinkage at the 35 mm and 150 mm ends of the U-shaped groove. The maximum shrinkage at 35 mm is 0.05 mm, the minimum is 0.02 mm, and the average shrinkage is 0.03 mm. The maximum shrinkage at 150 mm is 0.08 mm, the minimum is 0.04 mm, and the average shrinkage is 0.05 mm. Example

[0067] 1) Composition ratio and ingot smelting

[0068] Table 3 Chemical composition of TC4 ingot of Example 2

[0069] Location Al V Fe C N O H surface 6.11 4.13 0.17 0.012 0.008 0.122 0.003 Heart 6.07 4.09 0.19 0.015 0.009 0.115 0.003

[0070] 2) The forging part has the same process specifications and dimensions

[0071] 3) Ф150×L mm for second heat rolling:

[0072] First fire temperature: T = 900 ~ 950 ℃, Ф150 × L mm rolled to Ф60 × L mm;

[0073] The second fire temperature is controlled at T=880~930℃, and the Ø60×L mm is rolled to Ø14.5×L mm;

[0074] 4) Hot draw the Ф14.5×L mm semi-finished bar to Ф14×L mm, ensure the drawing deformation, control the temperature, further refine the grains, optimize the internal structure, and control the residual stress level.

[0075] 5) Strip the Ø14×L mm bar to Ø13.0×L mm on a centerless lathe to remove the surface oxide scale and surface defects of the bar.

[0076] 6) The Ф13.0×L mm bar is heated to 700~850℃ for recrystallization and kept at this temperature for 1~2h for complete annealing process. The grains inside the billet are recrystallized to form a fine and uniform equiaxed structure, which completely eliminates the residual stress inside the structure. The cooling method adopts furnace cooling to below 500℃ and then air cooling to avoid thermal stress inside the material during rapid cooling.

[0077] 7) After annealing, tensile force is applied to both ends of the bar and it is clamped by an electric straightening machine for heating and straightening, which avoids the problem of residual compressive stress caused by the original process; at the same time, the small amount of axial tensile stress generated by the electric heating process is eliminated by low-temperature tempering again after straightening.

[0078] 8) After the straightening by electric heating, the rod is subjected to stress relief annealing at 480~700℃ for 2~5h to further homogenize the internal structure of the titanium alloy rod. At the same time, the internal structure is precipitated with fine dispersed α phase through long-term heat preservation at low temperature, so that the uniformity and stability of the structure are better, and the internal stress is further released and balanced, thereby achieving an extremely low internal stress level. After stress relief annealing, the semi-finished rod is quickly cooled to below 150℃ with the furnace to avoid the generation of residual stress again.

[0079] 9) The straightened bars are machined, ground, and polished in multiple passes with small amounts to a finished product of Ф12×L mm (single pass grinding amount ≤ 0.15 mm).

[0080] 10) Detect the shrinkage. Take 10 sample bars with a length of 240 mm from the bar material, and process a U-shaped groove with a processing depth of 150 mm and a width of 6 mm along the axial direction with the center of the end face as the center. Measure the shrinkage at 35 mm and 150 mm (end) of the U-shaped groove. The maximum shrinkage at 35 mm is 0.06 mm, the minimum is 0.03 mm, and the average shrinkage is 0.04 mm. The maximum shrinkage at 150 mm is 0.08 mm, the minimum is 0.05 mm, and the average shrinkage is 0.06 mm.

[0081] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A TC4 titanium alloy bar for pedicle screws, characterized in that: The chemical composition of the TC4 titanium alloy is calculated by mass fraction, and the main components include 6.07 to 6.11 Al, 3.98 to 4.13 V, 0.16 to 0.19 Fe, 0.012 to 0.015 C, 0.008 to 0.009 N, 0.105 to 0.122 O, and 0.003 to 0.004 H; the balance is Ti; the Ti raw material is high-quality grade 0 sponge titanium; the processing method of the TC4 titanium alloy bar comprises the following steps: Step 1: Use high-quality pre-melted master alloy to automatically mix the materials; use a vacuum consumable arc furnace to repeatedly melt three times to form a TC4 titanium alloy ingot; Step 2: The TC4 titanium alloy ingot is subjected to three-time reversing upsetting and forging by combining β forging with two-phase zone forging, and the forging temperature is 900-1150°C; Step 3: After forging, the steel is rolled for more than two times, with a rolling temperature of 880~950℃ and a deformation rate of ≥60%; Step 4: After rolling, hot drawing is performed. The hot drawing deformation temperature is 870~920℃, and the deformation amount is: 5%~25%; Step 5: Heat the semi-finished bar after hot drawing to above the recrystallization temperature for complete annealing, the annealing temperature is 700~850℃, and the annealing time is 1~2h; after annealing, use furnace cooling to below 500℃ and then air cooling; Step 6: Electric heating straightening is performed by heating and straightening, and tempering is performed again after straightening; Step 7: Stress relief annealing, the stress relief annealing temperature is 480~700℃ and kept warm for 2~5h. After the stress relief annealing is completed, the semi-finished bar is cooled to below 150℃ with the furnace; Step 8: Grinding is performed through multiple passes with small processing volume, and the single pass grinding volume is ≤0.15mm.

2. The TC4 titanium alloy rod for pedicle screws according to claim 1, characterized in that: In step 2 of the processing method of the TC4 titanium alloy bar, the temperatures of the three-fire reversing upsetting and drawing forging are 1050-1150°C, 1000-1050°C, and 900-1000°C, respectively.

3. The TC4 titanium alloy rod for pedicle screws according to claim 1, characterized in that: In step 3 of the processing method of the TC4 titanium alloy bar, the second rolling temperatures are 900-950°C and 880-930°C respectively.

Citation Information

Patent Citations

  • Preparation method of titanium alloy bar of universal resetting screw seat

    CN111534715A